The relationship between the ratio of the supraspinatus muscle thickness measured by ultrasound imaging and glenohumeral subluxation in stroke patients: a cross-sectional study - Xie, Hualong; Zhang, Qing; Zhan, Jiawen; Dong, Jige; Chen, Jing; Kang, Guoxin; Liu, Huilin; Huang, Qiuchen; Zhu, Liguo; Onoda, Ko; Maruyama, Hitoshi; Liu, Shan; et al. (Frontiers in Neurology, 2024)
Introduction: Glenohumeral subluxation (GHS) is a common complication in stroke patients with hemiplegia, occurring in approximately 17-81% of cases. This study aims to evaluate the relationship between shoulder muscle thickness and the degree of subluxation using ultrasound imaging. Methods: A cross-sectional study of 61 stroke patients with hemiplegia was conducted, measuring supraspinatus muscle thickness, deltoid muscle thickness, and acromion-greater tuberosity (AGT). Logistic regression and ROC analyses were used. ROC curves, calibration plots, and decision curves were drawn on the training and validation sets. Results: According to logistic regression analysis, the ratio of supraspinatus muscle thickness was statistically significant (OR: 0.80; 95% CI: 0.70-0.92; p < 0.01), and it was an independent factor for evaluating the presence or absence of GHS. An AUC of 0.906 (95% CI: 0.802-1.000) was found in the training set; meanwhile, the AUC in the validation set was 0.857 (95% CI: 0.669-1.000), indicating good performance (Figs. 3 and4). According to the training set ROC curve, the most effective statistical threshold was 93%, with a sensitivity of 84% and a specificity of 96%. Discussion: The ratio of supraspinatus muscle thickness is a valuable criterion for evaluating GHS risk, supporting targeted rehabilitation interventions..